Evaluation of Bacterial Contamination in Clinical Environment of Sari Dental School in 2018 - N Hoshyari; Z Allahgholipour; M Ahanjan; M Moosazadeh; M zamanzadeh (Islamic Azad University, 2019)
Background and Aim: Bacterial contamination of clinical surfaces of dental units that have been touched or been exposed to patients' blood or saliva can be a reservoir for infections, leading to cross-contamination. This study aimed to evaluate bacterial contamination in the clinical environment of Sari Dental School in 2018. Materials and Methods: In this cross-sectional (descriptive-analytical) study, samples were randomly collected from 15 active dental units of five departments of Sari Dental School, including surgical, pediatrics, prosthodontics, endodontics, and restorative dentistry departments. Samples were collected from headrests, light handles, and dental seats using moist sterile swabs, and air samples were collected using agar plates. Sampling was carried out before and after dental practice. The samples were transferred to the microbiology laboratory to determine the number of various microorganism colonies. Data were analyzed using Chi-square, McNemar, and Kruskal-Wallis tests. P-values lower than 0.05 were considered significant. Results: A significant difference was found between the frequency of contamination before and after clinical practice based on McNemar test results. Staphylococci were more prevalent on the surfaces. Kruskal-Wallis test revealed no significant difference in the total number of microorganisms between different departments after dental practice. Bacterial contamination of air was greater than other parts, followed by dental seats. Conclusion: Microbial contamination of dental units considerably increases after treatment of each patient. Therefore, disinfection of dental unit surfaces and seats between each patient is essential. Also, methods of infection control must be supervised to prevent cross-infection.